(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2015)
Why have states, in a somewhat short period of time (1995-2005), suddenly decided to “cooperate” regarding global infectious disease surveillance? What kind of “cooperation” is it? Why did states apparently surrender part of their sovereign power to the WHO by giving it the power to declare pandemic at the global scale without state consent? These questions appear especially relevant in the context where issues of health and diseases at the global scale have been explicitly linked with the concepts of “risk”, “security”, “emergency”, “crisis”, “intelligence”, and “terrorism”. The objective of this article is to start answering these questions by first of all looking at the problems and paradoxes of the practices of Global Health Security through an analysis of the microbial space, capitalistic cooperation, and the production of information and data about health security. Secondly, the article draws the attention to the politics behind the structuration of Global Health Security as a social evidence by looking at contested concepts that represent promising research avenues.